Kepastian Hukum Terhadap Jabatan Notaris Yang dinyatakan Pailit - Nabila Aulia Putri (Dinasti Research, 2025)
Bankruptcy regulations in Law Number 37 of 2004 as amended by Law Number 2 of 2014 concerning Notary Positions, especially Article 12 letter a, cause different interpretations and conflict with bankruptcy regulations regulated in Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. So this research aims to further analyze bankruptcy in the position of Notary. The type of research used is a doctrinal approach using a statutory approach and using primary legal materials and secondary legal materials. The research results concluded that Article 12 letter a of the Law on the Position of Notaries provides legal implications that a Notary will be dishonorably dismissed if the Notary is declared bankrupt by the Court. Meanwhile, in the Law on Bankruptcy and Suspension of Debt Payment Obligations, the consequences of bankruptcy only relate to the debtor's assets and the debtor still has civil rights such as carrying out his position or profession.